The place of allogeneic stem cell transplantation in aggressive B-cell non-Hodgkin lymphoma in the era of CAR-T-cell therapy - Castagna, Luca; Bono, Roberto; Tringali, Stefania; Sapienza, Giuseppe; Santoro, Alessandra; Indovina, Alessandro; Tarantino, Vittoria; Di Noto, Laura; Maggio, Aurelio; Patti, Caterina (Frontiers in Medicine, 2022)
Chimeric antigen receptor T (CAR-T) cells are a treatment option for patients with relapse/refractory (R/R) non-Hodgkin lymphoma (NHL), acute lymphoid leukaemia and multiple myeloma. To date, diffuse large B-cell lymphoma (DLBCL), mantle cell lymphoma (MCL), follicular lymphoma (FL), and chronic lymphocytic leukaemia (CLL) have been successfully treated with CAR-T cells directed against the CD19 antigen. However, when R/R disease persists after several treatment lines, patients with these diseases are often referred to transplantation centres to receive allogeneic stem cell transplantation (ALLO-SCT). ALLO-SCT and CAR-T cells share mechanism of actions, inducing immune effects of T cells (and other cells after transplantation) against lymphoma cells, but they differ in several other characteristics. These differences justify unique positioning of each therapy within treatment algorithms. In this paper, we analysed the results obtained after ALLO-SCT and CAR-T-cell therapy in patients with aggressive lymphomas (large B-cell lymphoma and MCL) to identify the ideal scenarios in which these 2 immunological therapies should be employed.